2019
DOI: 10.1177/1460458219871135
|View full text |Cite
|
Sign up to set email alerts
|

Highlighting the rules between diagnosis types and laboratory diagnostic tests for patients of an emergency department: Use of association rule mining

Abstract: Diagnostic tests are widely used in emergency departments to make detailed investigations on diagnosis and treat patients correctly. However, since these tests are expensive and time-consuming, ordering correct tests for patients is crucial for efficient use of hospital resources. Thus, understanding the relation between diagnosis and diagnostic test requirement becomes an important issue in emergency departments. Association rule mining was used to extract hidden patterns and relation between diagnosis and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 30 publications
(38 reference statements)
1
27
0
2
Order By: Relevance
“…Previous studies have shown that pain and discomfort and neuroendocrine changes caused by chronic diseases cause changes in the transmitters of the central nervous system, thereby inducing the depression. Basically all patients with chronic diseases are accompanied by varying degrees of mental dysfunction, and the most frequent occurrence is depression [24][25][26]. All in all, mental illnesses and CKD recovery interact with each other.…”
Section: Factors Affecting Mental Health Of Patientsmentioning
confidence: 99%
“…Previous studies have shown that pain and discomfort and neuroendocrine changes caused by chronic diseases cause changes in the transmitters of the central nervous system, thereby inducing the depression. Basically all patients with chronic diseases are accompanied by varying degrees of mental dysfunction, and the most frequent occurrence is depression [24][25][26]. All in all, mental illnesses and CKD recovery interact with each other.…”
Section: Factors Affecting Mental Health Of Patientsmentioning
confidence: 99%
“…Association rule mining is another technique used to discover and formulate rules around frequent patterns in a dataset. Association rule mining has been used to discover relations between different types of diseases and diagnostic tests in the emergency department to make decisions and plan operations more efficiently [32].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the Apriori algorithm in ARM was frequently used in healthcare services to generate association rules between clinical events and various medications, tests, and other relations [7,31]. Among the tasks of interest of ARM in medical applications were identifying risks [27,32], understanding factors [33,34], discovering patterns [7,12], clinical decision support systems [35,36], feature selection [37], and prediction/classification [38].…”
Section: The Arm In Medical Applicationmentioning
confidence: 99%
“…The study found that females had a lower risk of heart disease, and the detail rules were extracted in terms of clinical measurement. Similarly, Sariyer [7] highlighted the relations between the type of diagnosis and laboratory tests conducted in emergency departments, known as the main units in hospitals, which were often overcrowded with patients. Due to the time consumption and high costs for conducting the laboratory tests, the understanding of this relation improved decision-making and efficiently utilised available resources.…”
Section: The Arm In Medical Applicationmentioning
confidence: 99%